Indigenous and commercial isolates of arbuscular mycorrhizal fungi display differential effects in Pyrus betulaefolia roots and elicit divergent transcriptomic and metabolomic responses - Shao, Yadong; Jiang, Shangtao; Peng, Haiying; Li, Han; Li, Peigen; Jiang, Rou; Fang, Wenyi; Chen, Tingsu; Jiang, Gaofei; Yang, Tianjie; Nambeesan, Savithri U.; Xu, Yangchun; et al. (Frontiers in Plant Science, 2023)
Background: Arbuscular mycorrhizal fungi (AMF) form beneficial obligate symbionts with many terrestrial plants. They help with acquisition of mineral nutrients and water to the plant in exchange for host-synthesized carbohydrates and lipids. Results: To investigate the function of indigenous AMF, we used two different ways to propagate the indigenous AMF to simulate spore propagation in natural soils. Root mycorrhizal colonization of white clover and arbuscular abundance in S (orchard soil with fine roots removed) were significantly higher than in R (orchard soil mixed with fine roots), but spore density and soil hyphal density after propagation were not significantly different between the treatments. To study the effects of indigenous AMF on root growth and metabolism of pear trees, we used ST (sterilized soil from CK in Trifolium repens mixed with sterilized standard soil), indigenous AMF (+R, soil from R in Trifolium repens mixed with sterilized standard soil; -R, soil from S in Trifolium repens mixed with sterilized standard soil), and two AMF isolates (Rhizophagus intraradices (Ri) and Glomus mosseae (Gm)) inoculated in the Pyrus betulifolia root to study the difference on plant growth, root morphology, mineral nutrient accumulation, metabolite composition and abundance, and gene expression. AMF treatment significantly increased growth performance, root morphology and mineral nutrient accumulation in this study, with the -R performing better. In addition, indigenous AMF and AMF isolates displayed both, common and divergent responses on metabolite and gene expression in pear roots. In this study, compared with ST, most types of flavones, isoflavones, and carbohydrates decreased in the AMF, whereas most types of fatty acids, fatty acyls, amino acids, glycerolipids, and glycerophospholipids increased in the AMF. Meanwhile, the relative abundance of amino acids, flavonoids and carbohydrates displayed different trends between indigenous AMF and AMF isolates. We found that Gm and -R treatment could induce different gene responses in root metabolic pathways resulting in enriched fructose and mannose metabolism (ko00051), fatty acid biosynthesis (ko00061) and flavonoid biosynthesis (ko00941). Conclusions: This study demonstrates that different effects in pear plant to indigenous AMF and AMF isolates were caused by a series of divergent responses from gene transcription to metabolite accumulation